Cultural variations in wellbeing, burnout and substance use amongst medical students in twelve countries. (17th February 2021) - Molodynski, Andrew; Lewis, Thomas; Kadhum, Murtaza; Farrell, Sarah Marie; Lemtiri Chelieh, Maha; Falcão De Almeida, Telma; Masri, Rawan; Kar, Anindya; Volpe, Umberto; Moir, Fiona; Torales, Julio; Castaldelli-Maia, João Mauricio; et al.
Abstract: High levels of stress, burnout, and symptoms of poor mental health have been well known among practicing doctors for a number of years. Indeed, many health systems have formal and informal mechanisms to offer support and treatment where needed, though this varies tremendously across cultures. There is increasing evidence that current medical students, our doctors of the future, also report very high levels of distress, burnout, and substance misuse. We sampled large groups of medical students in 12 countries at the same time and with exactly the same method in order to aid direct comparison. 3766 students responded to our survey across five continents in what we believe is a global first. Our results show that students in all 12 countries report very high levels of 'caseness' on validated measures of psychiatric symptoms and burnout. Rates of substance misuse, often a cause of or coping mechanism for this distress, and identified sources of stress also varied across cultures. Variations are strongly influenced by cultural factors. Further quantitative and qualitative research is required to confirm our results and further delineate the causes for high rates of psychiatric symptoms and burnout. Studies should also focus on the implementation of strategies to safeguard and identify those most at risk.